Spinal Schwannomatosis Unassociated with Phakomatosis: A Case Report (2021)
Schwannomas are slow-growing, encapsulated benign tumors of the peripheral nerves. The multiplicity of these tumors has been linked with genetic anomalies associated with neurofibromatosis. Schwannomatosis is a rare autosomal-dominant tumor syndrome characterized by the occurrence of multiple schwannomas of the peripheral nervous system, with no involvement of the vestibular nerve. This contrasts with neurofibromatosis 2, in which the existence of bilateral vestibular schwannomas is pathognomonic. Spinal schwannomatosis without features of neurofibromatosis is a very rare occurrence, previously unreported in Nigerian neurosurgical literature. We present a Nigerian patient with cervical intradural-extramedullary and thoracic intramedullary spinal schwannomas. His treatment outcome and a brief literature review were also discussed.